2018
DOI: 10.1002/mame.201800169
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Mechanical Properties of FDM‐PLA Parts via Thermal Annealing

Abstract: The objective of this study is to investigate the possibility of enhancing mechanical properties of poly(lactic acid) (PLA) samples processed by a rapid manufacturing (RM) technique by increasing PLA crystallinity degree via thermal annealing. The samples are manufactured by fused deposition modeling (FDM) at different temperatures and subsequently evaluated by three‐point bending flexural and tensile tests. The polymer processed at 215 °C is thermally annealed over its glass transition temperature in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(110 citation statements)
references
References 40 publications
7
94
0
9
Order By: Relevance
“…Similarly, halving the print speed has little to no impact on the melting enthalpy values. As a matter of fact, Conditions 1, 3, 4, and 5 possess very similar degrees of crystallinity after the third zone due to the fact that they all experience a similar thermal history during the third zone with a T build plate of 110 • C. Findings by other authors support these trends [43][44][45][46][47]. The large difference in melting enthalpy between Condition 6 using LMWPA and the conditions printed with HMWPA illustrates the substantial effect of a decrease in molecular weight on the total degree of crystallinity that is developed over the course of the FFF process, already demonstrated in the literature for PLA [30].…”
Section: Approximation Of Thermal Profiles and Simulation In Fscmentioning
confidence: 63%
See 1 more Smart Citation
“…Similarly, halving the print speed has little to no impact on the melting enthalpy values. As a matter of fact, Conditions 1, 3, 4, and 5 possess very similar degrees of crystallinity after the third zone due to the fact that they all experience a similar thermal history during the third zone with a T build plate of 110 • C. Findings by other authors support these trends [43][44][45][46][47]. The large difference in melting enthalpy between Condition 6 using LMWPA and the conditions printed with HMWPA illustrates the substantial effect of a decrease in molecular weight on the total degree of crystallinity that is developed over the course of the FFF process, already demonstrated in the literature for PLA [30].…”
Section: Approximation Of Thermal Profiles and Simulation In Fscmentioning
confidence: 63%
“…By using conventional Differential Scanning Calorimetry (DSC) and X-ray Diffraction (XRD), the crystallinity in the final printed part is examined showing little impact of the liquefier temperature, yet a large effect of increasing the build plate temperature. Annealing the printed part, either by the build plate heated sufficiently above the glass transition temperature (T g ) or as a follow-up treatment, has been proven to enhance crystallinity strongly [43][44][45][46][47]. The continuous successive deposition of new molten polymer onto previously printed layers results in consecutive annealing cycles, ultimately producing a gradient of crystallinity in the printed part with upper layers, having been exposed to fewer annealing cycles, being less crystalline.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties are an important parameter of FDM printed general polymer parts and depend on filament bonding influenced by slicing parameters, building orientation and temperature conditions [ 33 ]. Wach et al demonstrated that the mechanical properties of FDM-PLA parts can be enhanced by thermal annealing [ 34 ]. Furthermore, the mechanical properties of polymers could be reinforced with discontinuous fibers.…”
Section: Additive Manufacturing (Am) Technologies For Four-dimensimentioning
confidence: 99%
“…Moreover, strengthening the crystallization kinetics of PLA not only alleviates the negative effect of low melt strength during processing but also improves the foamability of PLA 16,17 . Enhanced crystallization can provide more heterogeneous cell nucleation sites, significantly promoting cell nucleation during gas saturation 18 …”
Section: Introductionmentioning
confidence: 99%